Measuring supports from learning assistants that promote engagement in active learning: evaluating a novel social support instrument - Dania Hernandez; Gema Jacomino; Uma Swamy; Krista Donis; Sarah L. Eddy (SpringerOpen, 2021)
Abstract Background Active learning supports student performance, but can be challenging to implement in large courses. The Learning Assistant (LA) Program is a growing intervention to support students in large active learning classrooms. This program places advanced undergraduates who have training in pedagogical methods in active learning classrooms to interact with and support students during in-class activities. LAs increase student performance, but the mechanism behind this is still unclear. Social support is a promising framework to help elucidate the types and extent of assistance LAs provide to students and begin exploring the "how" behind LAs effectiveness. The aim of this study was to develop an instrument measuring undergraduate students' perceptions of the social supports for active learning available to them in the classroom. This instrument was based on both the broader social support literature and the literature on what factors encourage students to engage deeply in active learning. To provide initial evidence of validity, the instrument was completed in six sections of General Chemistry I at one R1 university. Exploratory and confirmatory factor analyses were applied to determine the internal structure of the instrument. Then the instrument's relationship to engagement in active learning was evaluated as another form of validity evidence. Results These analyses best supported a three-factor instrument that included five items representing supportive feedback provided during active learning (appraisal support), eight items representing emotional support during active learning, and six items representing the communications of norms and values related to active learning (informational support). All three factors were individually correlated with three measures of engagement. In regression analyses with all three factors measured together, only informational support predicted changes in two of the three measures of engagement. Conclusions This study supports the use of the Perception of Social Supports for Active Learning (PSSALI) instrument to understand students' perceptions of the supports they are receiving to engage in active learning in chemistry courses. One implication of this work is that in order to increase engagement, learning assistants should clearly communicate the value of active learning and the classroom norm of active participation.